2017
DOI: 10.1111/imm.12771
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CD4 T cells and their effects on immunopathological inflammation following viral infection

Abstract: CD4 T cells help immune responses, but knowledge of how memory CD4 T cells are regulated and how they regulate adaptive immune responses and induce immunopathology is limited. Using adoptive transfer of virus-specific CD4 T cells, we show that naive CD4 T cells undergo substantial expansion following infection, but can induce lethal T helper type 1-driven inflammation. In contrast, memory CD4 T cells exhibit a biased proliferation of T follicular helper cell subsets and were able to improve adaptive immune res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Therefore, it is advisable to transfer between 10 4 and 10 5 SMARTA cells to be able to visualize them after viral infection. A critical consideration is that injection of >10 6 naïve SMARTA cells can result in immunopathology after chronic LCMV Cl-13 challenge (Bhattacharyya et al, 2017a (Fallet et al, 2016;Moseman, Wu, de la Torre, Schwartzberg, & McGavern, 2016;Sammicheli et al, 2016). Therefore, it is advisable to adoptively transfer high numbers (>5 × 10 6 ) of KL25 B cells to allow their detection in vivo.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, it is advisable to transfer between 10 4 and 10 5 SMARTA cells to be able to visualize them after viral infection. A critical consideration is that injection of >10 6 naïve SMARTA cells can result in immunopathology after chronic LCMV Cl-13 challenge (Bhattacharyya et al, 2017a (Fallet et al, 2016;Moseman, Wu, de la Torre, Schwartzberg, & McGavern, 2016;Sammicheli et al, 2016). Therefore, it is advisable to adoptively transfer high numbers (>5 × 10 6 ) of KL25 B cells to allow their detection in vivo.…”
Section: Methodsmentioning
confidence: 99%
“…PD-1-based immunotherapy for the treatment of chronic infection was first shown in the chronic LCMV Cl-13 model (Barber et al, 2006), and was then shown to also be effective in the SIV model in macaques (Velu et al, 2009). Many studies on immune regulation have utilized the LCMV system (Bhattacharyya et al, 2017b;Bhattacharyya & Penaloza-MacMaster, 2017, 2018Im et al, 2016;Kamphorst et al, 2017;Penaloza-MacMaster et al, 2011;Penaloza-MacMaster, Kamphorst et al, 2014;Penaloza-MacMaster, Masopust, & Ahmed, 2009;Penaloza-MacMaster, Provine, Blass, & Barouch, 2015;Penaloza-MacMaster, Teigler et al, 2014;Vezys et al, 2011;Wang et al, 2019;West et al, 2013;West et al, 2011).…”
Section: Intravenous Infectionmentioning
confidence: 99%
See 3 more Smart Citations